HERBAL MORINGA TEA COUNSELING FOR PREVENTING STUNTING IN TODDLERS AND PREGNANT WOMEN - Hani Setyaputri, Nabila; Vicky Saifudin N, Muhamad; Rachmadira Putri, Kania; Haikal, Hikam; Ayu Eryani, Rambu; Ahfas, Akhmad (Antis-publisher, 2025)
Objective: This study aims to explore the utilization of Moringa oleifera leaves as a nutritional intervention to prevent and reduce stunting among toddlers through the development of Moringa herbal tea. Method: A community-based education and training program was conducted involving members of the Family Welfare Empowerment (PKK) g roup. The program included stages of preparation, implementation, and evaluation, focusing on knowledge transfer regarding the nutritional benefits of Moringa leaves and hands-on training in herbal tea production. Results: The training significantly improved participants’ understanding of the nutritional content and processing techniques of Moringa leaves, particularly their rich composition in protein, beta-carotene, calcium, iron, magnesium, vitamin C, and vitamin A, along with potent antioxidant compounds. Novelty: This initiative presents a localized and sustainable approach by empowering community members—especially women—as agents of change in combating malnutrition and stunting, through the production and promotion of Moringa-based functional beverages. The integration of traditional knowledge with scientific insight into nutrition showcases an innovative model of health promotion at the grassroots level.